Impact of Early Life Socioeconomic Status on Decision Making in Older Adults Without Dementia. (July 2021) - Weissberger, Gali H.; Han, S. Duke; Yu, Lei; Barnes, Lisa L.; Lamar, Melissa; Bennett, David A.; Boyle, Patricia A.
Highlights: We examined the effect of early life socioeconomic status (SES) on decision making. A positive association between early life SES and decision making was found. The relationship was strongest in those with low financial and health literacy. Early life SES is associated with decision making in non-demented older adults. Improving literacy may buffer the impact of early life SES on decision making. Abstract: Objectives: A growing body of evidence points to the negative impact of early life socioeconomic status (SES) on health and cognitive outcomes in later life. However, the effect of early life SES on decision making in old age is not well understood. This study investigated the association of early life SES with decision making in a large community-based cohort of older adults without dementia from the Rush Memory and Aging Project. Materials and Methods: Cross-sectional data from the Rush Alzheimer's Disease Center Memory and Aging Project was analyzed. Participants were 1044 community-dwelling older adults without dementia ( M age = 81.15, SD = 7.49; 75.8% female; 5.4% non-White). Measures of financial and healthcare decision making and early life SES were collected, along with demographics, global cognition, and financial and health literacy. Results: Early life SES was positively associated with decision making (estimate = 0.218, p = 0.027), after adjustments for demographic covariates and global cognition, such that a one-unit increase in early life SES was equivalent to the effect of being four years younger in age as it pertains to decision making. A subsequent model demonstrated that the relationship was strongest in those with low literacy, and weakest for those with high literacy (estimate = -0.013, p = 0.029). Conclusions: Findings from this study suggest that early life SES is associated with late life decision making and that improving literacy, a modifiable target for intervention, may buffer the negative impact of low early life SES on decision making in older adulthood.